THE EFFECT OF RAW MATERIALS ON SOME PHYSICAL PROPERTIES OF OSUN STATE CERAMIC TILES - OLURANTI ABIOLA; ADEKOLA OKE; BABATUNDE OMIDIJI; DARE ADETAN (Journal of Engineering Studies and Research)
The study evaluates the effect of ceramic raw materials on the physical properties of ceramic tiles with a view to determine the tiles with the best material blend. Ten different blends of clay – feldspar – silica was used to produce ceramic samples. The results show that sample with 60 % clay, 30 % feldspar and 10% silica have the best water absorption (10.43%) and apparent porosity (22.77 %); while sample with 60 % clay, 20 % feldspar and 20 % silica exhibits the highest apparent relative density of 2.79. Sample with 50 % clay, 40 % feldspar and 10 % silica possesses the best bulk density of 1.43 g/cm3. Conclusively, the ceramic sample produced can be useful in the production of wall tiles.